# Question:Simplification of Gamma function

## Question:Simplification of Gamma function

Maple

Dear Users!

I want to simple the Gamma function occures in a matrix. I need the simpliest form of this matrix. If there is some thing common in all entries take it common. Thanks

Matrix(6, 6, {(1, 1) = 2*GAMMA(alpha+5/2)*Pi^(1/4)*sqrt(GAMMA(alpha+1)*GAMMA(alpha+1/2)^3)/(alpha*(2*alpha+3)*(1+2*alpha)*GAMMA(alpha)*GAMMA(alpha+1/2)^2), (1, 2) = 0, (1, 3) = 0, (1, 4) = 0, (1, 5) = 0, (1, 6) = 0, (2, 1) = (1/2)*GAMMA(alpha+5/2)*Pi^(1/4)*sqrt(GAMMA(alpha+1)*GAMMA(alpha+1/2)^3)/(alpha*(2*alpha+3)*(1+2*alpha)*GAMMA(alpha)*GAMMA(alpha+1/2)^2), (2, 2) = (1/4)*GAMMA(alpha+5/2)*sqrt(2)*sqrt(GAMMA(alpha+1/2)^3*alpha^3*(alpha+1)^3*GAMMA(alpha)^3)*Pi^(1/4)/((2*alpha+3)*(1+2*alpha)*GAMMA(alpha+1/2)^2*alpha^2*(alpha+1)^2*GAMMA(alpha)^2), (2, 3) = 0, (2, 4) = 0, (2, 5) = 0, (2, 6) = 0, (3, 1) = (1/16)*GAMMA(alpha+5/2)*Pi^(1/4)*sqrt(GAMMA(alpha+1)*GAMMA(alpha+1/2)^3)/(GAMMA(alpha+1/2)^2*alpha*(alpha+1)*(1+2*alpha)*GAMMA(alpha)), (3, 2) = (1/8)*GAMMA(alpha+5/2)*sqrt(2)*sqrt(GAMMA(alpha+1/2)^3*alpha^3*(alpha+1)^3*GAMMA(alpha)^3)*Pi^(1/4)/((2*alpha+3)*(1+2*alpha)*GAMMA(alpha+1/2)^2*alpha^2*(alpha+1)^2*GAMMA(alpha)^2), (3, 3) = (1/32)*GAMMA(alpha+5/2)*sqrt(2)*sqrt(alpha^3*GAMMA(alpha+3/2)^3*(2+alpha)^3*GAMMA(alpha)^3)*Pi^(1/4)/((alpha+1)*(2*alpha+3)*alpha^2*GAMMA(alpha+3/2)^2*(2+alpha)^2*GAMMA(alpha)^2), (3, 4) = 0, (3, 5) = 0, (3, 6) = 0, (4, 1) = 0, (4, 2) = 0, (4, 3) = 0, (4, 4) = 2*GAMMA(alpha+5/2)*Pi^(1/4)*sqrt(GAMMA(alpha+1)*GAMMA(alpha+1/2)^3)/(alpha*(2*alpha+3)*(1+2*alpha)*GAMMA(alpha)*GAMMA(alpha+1/2)^2), (4, 5) = 0, (4, 6) = 0, (5, 1) = 0, (5, 2) = 0, (5, 3) = 0, (5, 4) = (3/2)*GAMMA(alpha+5/2)*Pi^(1/4)*sqrt(GAMMA(alpha+1)*GAMMA(alpha+1/2)^3)/(alpha*(2*alpha+3)*(1+2*alpha)*GAMMA(alpha)*GAMMA(alpha+1/2)^2), (5, 5) = (1/4)*GAMMA(alpha+5/2)*sqrt(2)*sqrt(GAMMA(alpha+1/2)^3*alpha^3*(alpha+1)^3*GAMMA(alpha)^3)*Pi^(1/4)/((2*alpha+3)*(1+2*alpha)*GAMMA(alpha+1/2)^2*alpha^2*(alpha+1)^2*GAMMA(alpha)^2), (5, 6) = 0, (6, 1) = 0, (6, 2) = 0, (6, 3) = 0, (6, 4) = (1/16)*(18*alpha+19)*GAMMA(alpha+5/2)*Pi^(1/4)*sqrt(GAMMA(alpha+1)*GAMMA(alpha+1/2)^3)/(alpha*(alpha+1)*(2*alpha+3)*(1+2*alpha)*GAMMA(alpha)*GAMMA(alpha+1/2)^2), (6, 5) = (3/8)*GAMMA(alpha+5/2)*sqrt(2)*sqrt(GAMMA(alpha+1/2)^3*alpha^3*(alpha+1)^3*GAMMA(alpha)^3)*Pi^(1/4)/((2*alpha+3)*(1+2*alpha)*GAMMA(alpha+1/2)^2*alpha^2*(alpha+1)^2*GAMMA(alpha)^2), (6, 6) = (1/32)*GAMMA(alpha+5/2)*sqrt(2)*sqrt(alpha^3*GAMMA(alpha+3/2)^3*(2+alpha)^3*GAMMA(alpha)^3)*Pi^(1/4)/((alpha+1)*(2*alpha+3)*alpha^2*GAMMA(alpha+3/2)^2*(2+alpha)^2*GAMMA(alpha)^2)})

﻿